Teknolojik değişim: Türkiye’de üretim araçları üretimi (1996-2005) - Narin, Özgür (My University, 2008)
TEKNOLOJK DEGSM: TÜRKYE’DE ÜRETM ARAÇLARI ÜRETM (1996-2005) 1980’lere kadar yaygın olan “sanayilesme” vurguları günümüzde yerini “teknolojik açıgı kapatma”, “yetisme” sözcüklerine bırakmıstır. Sermaye birikimi perspektifinden far kopartılmıs; büyümenin motoru, zenginligin ve degerin kaynagı olarak yeniden tılsımlı bir degnek haline getirilmistir. Buna karsılık bu tezde teknoloji, kapitalist üretim sürecine dönüsen bilim üretiminin bir ürünü olarak analiz edilmistir. Bilim ve teknolojinin üretim süreci sermaye birikimi perspektifiyle ele alınmıstır. Bu baglamda 1996-2005 yılları arasında Türkiye’de üretim araçları üretimi incelenmistir. Bu dönemde teknolojik düzeyi yüksek olan yatırım malları üretiminin payındaki göreli artısın üretim araçları üretimine aynı biçimde yansımadıgı gösterilmistir. Teknoloji üretimi esas olarak üretim araçları üretiminin geri baglantısı olarak gelisebilirken, bu dönemde bu geri baglantının zayıf oldugu gösterilmistir. Teknoloji politikalarının 1996’dan önce etkin olarak uygulanamamasında oldugu gibi 1996 sonrası belirli sermaye kesimlerinin ihtiyaçlarına yönelik uygulanmasında, yönetim hatası degil, sermaye birikimi belirleyicidir.

TECHNOLOGICAL CHANGE: PRODUCTION OF MEANS OF PRODUCTION IN TURKEY (1996-2005) Nowadays “catching up” and “reducing the technology gap” are the two alternatives that take the place of the term “industrialisation” which was used widely untill 1980s. Similarly today technology is understood as if it is a magic wand. It is seen as the engine of growth or taken as the source of all value and wealth. Common point of all these approaches is that they separate technology from capital accumulation. But in this thesis, technology is analyzed as the output of scientific production which itself becomes a capitalist production process. The production process of science and technology is analyzed from the perspective of capital accumulation. From this point of view, production of means of production in Turkey between 1996- 2005 is investigated in this thesis. Capital goods sector which has relatively higher technological level grows faster in this period. But production of means of production sector does not grow so fast. Since the production of technology is possible essentially as backward linkage of production of means of production, this thesis shows that this backward linkage is weak in this period. So it is not the technology policies that changes the structure of production. In contrast capital accumulation determines the technological structure of production.
Keywords: Teknolojik Değişim; Türkiye_Üretim Araçları